Effects of probiotics on neurodegenerative diseases - Córdova, Juan G.; Freile, Edison H.; Acosta, Prisca del P.; Cañarte, Paolo T.; Castillo, José N.; Núñez, Ma A.; Andrade , Melpisa P. (International Journal of Research in Medical Sciences, 2025)
Neurodegenerative diseases, including Alzheimer’s disease, Parkinson’s disease, and multiple sclerosis, represent a growing public health challenge due to their high prevalence and the lack of curative therapies. In this context, research on the gut–brain axis has highlighted the crucial role of the intestinal microbiota in modulating neurological processes and in the pathophysiology of these disorders. Probiotics, defined as live microorganisms that, when administered in adequate amounts, confer health benefits to the host, have shown potential neuroprotective effects. Preclinical and clinical studies have demonstrated that probiotics may modulate neuroinflammation, reduce oxidative stress, improve blood–brain barrier integrity, and regulate the production of neurotransmitters such as serotonin, GABA, and dopamine. In Parkinson’s disease, the administration of Lactobacillus and Bifidobacterium strains has been associated with improvements in gastrointestinal symptoms and reductions in systemic inflammatory markers. In Alzheimer’s disease, probiotic supplementation has been linked to benefits in cognitive parameters and decreases in inflammatory biomarkers. Likewise, in multiple sclerosis models, probiotics appear to modulate immune responses by promoting an anti-inflammatory profile. Although current findings are promising, the heterogeneity of probiotic strains, variability in study designs, and the limited number of controlled clinical trials highlight the need for further research to establish standardized protocols. Incorporating probiotic-based therapies may represent a complementary approach in the prevention and management of neurodegenerative diseases within the framework of personalized and interdisciplinary medicine.